2018
DOI: 10.1159/000490497
|View full text |Cite
|
Sign up to set email alerts
|

BAIBA Attenuates the Expression of Inflammatory Cytokines and Attachment Molecules and ER Stress in HUVECs and THP-1 Cells

Abstract: Objective: β-Aminoisobutyric acid (BAIBA), a myokine, is a thymine catabolite that is induced during exercise, leading to browning of white fat, hepatic fatty acid oxidation, and suppression of hepatic lipogenesis. However, the effects of BAIBA on the progression of atherosclerosis remain unclear. Methods: We performed a Western blot analyses to determine various protein expression. ELISAs (enzyme-linked immunosorbent assays), cell adhesion assays, and cell viability assays were also performed on human umbilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The levels of BAIBA have also been found to be elevated in the plasma of subjects following exercise and muscle-specific PGC-1α transgenic mice [13], indicating its role in mediating the beneficial effects of exercise. Consistent with these findings, previous reports have also suggested that BAIBA plays an anti-inflammatory role in various peripheral organs that are metabolically active [15,29,30]. The hypothalamus is the central unit that controls the whole-body energy metabolism by integrating multiple afferent inputs originating from the brain and peripheral organs [1,2].…”
Section: Discussionsupporting
confidence: 75%
“…The levels of BAIBA have also been found to be elevated in the plasma of subjects following exercise and muscle-specific PGC-1α transgenic mice [13], indicating its role in mediating the beneficial effects of exercise. Consistent with these findings, previous reports have also suggested that BAIBA plays an anti-inflammatory role in various peripheral organs that are metabolically active [15,29,30]. The hypothalamus is the central unit that controls the whole-body energy metabolism by integrating multiple afferent inputs originating from the brain and peripheral organs [1,2].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have reported elevated BAIBA in plasma after exercise training intervention in both human and mice studies 15 , exercise also increases GABA levels in brain 56 , gastrocnemius and quadriceps 7 , and systemic circulation 7 . Exercise stimulates the generation of these active compounds from muscle, which can further modulate browning of white fat and insulin resistance 15 , regulate osteoblastogenesis and osteoclastogenesis 40 , prevent loss of bone mass and muscle function 9,18 , suppress production of proinflammatory cytokines 57 , and play an important role on bone health 58 . In our study, the circulating concentrations of two isomeric aminobutyric acids, D-BAIBA and GABA, showed positive associations with physical activity in population of 136 young to middle-aged female individuals with low or high hip BMDs, lean mass, but no association in obese women (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an AMPK activator metformin ameliorates systemic inflammation through inhibiting C-reactive protein and IL-6 in patients with metabolic syndrome [35]. Jung et al have reported that myokine BAIBA alleviates LPS-induced inflammatory responses in HUVEC and THP-1 cells through the AMPK-mediated pathway [36]. Moreover, myokine fibronectin type III domain containing 4 (FNDC4) ameliorates lipid-induced inflammation and insulin resistance in adipocytes through AMPK-dependent signalling [16].…”
Section: Discussionmentioning
confidence: 99%